The Effect of Fragrances of Lavender on the Quality of Sleep, Mood, Team Cohesion and Performance of Women Volleyball Players - Fariba Mehdifar; Rokhsareh Badami; Zohre Meshkati (Institue of Medicinal Plants, ACECR, 2019)
Background: Lavender is one type of medicinal plants which have long been used for different purposes. Objective: The purpose of this study is to investigate the effect of fragrances of Lavender on the Quality of Sleep, Mood, Team Cohesion and Performance of Women Volleyball Players. Methods: The participants in this study were 24 women volleyball players from Junior Clubs First Championship League, whom were selected by easy-access method and grouped into two Experimental and Control groups. The experimental group smelled lavender for 21 sessions and 20 minutes for each session. The control group used placebo in this period. Before and after the intervention, data were gathered using Pittsburgh Sleep Quality Questionnaire, Brunel Emotional Questionnaire, Carron, Widemeyer and Brawley, Team Cohesion Questionnaire, Volleyball Service Accuracy Test of AAHPERD and Sargent Jump. Results: Data were analyzed using co-variance. Findings showed that smelling lavender could have a positive effect on quality of the sleep, mood and group cohesion. However, it had no effect on the performance. Conclusion: Findings of the study show that the fragrance of Lavender could have an integral effect on improving quality level of the sleep, mood and group cohesion of sports team athletes.